Model Pembelajaran Kisah Qurani - Nofitayanti Nofitayanti; Aulia Fitri (Journal on Education, 2022)
This paper is a literature review that discusses the learning model of Quranic stories to regenerate the treasures of knowledge about learning models, especially the Quranic model. In this article the aspects of the study discussed include: Definition of Quranic stories, types of Quranic stories, the purpose and benefits of Quranic stories, the impact of Quranic stories, the advantages of Quranic stories as well as principles and steps for using the model of Quranic stories in schools which will be concluded later and discussed in the last chapter. In this study the authors found that the Quranic story model, which seeks to adopt good stories and Islamic and Quranic examples in learning, is a solution offer to shape the character of students, especially in PAI subjects. Besides being able to shape character, Quranic stories can also bring teachers and students closer together as well as a counterbalance to television shows. The application of the Quranic story model can be integrated into learning Islamic Religious Education material by including it in PAI materials related to the story, accompanied by identification of the character values ​​contained therein.